2007
DOI: 10.1021/la701652m
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Pinning of Liquids through Inelastic Wetting Ridge Formation on Thermally Stripped Acrylic Polymers

Abstract: A film composed of a thermal-stripped, solvent-borne acrylic polymer is shown to completely arrest motion of the three-phase line for water as a result of ridge structure formation. This mechanism produces anomalous wetting behavior including the arbitrary selection of contact angles, formation of quasi-periodic ridge structures on surfaces, and requirement of stick and break motion for wetting line advancement, a novel mechanism reported here. The ridges are retained by the polymer subsequent to wetting, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 30 publications
1
44
1
Order By: Relevance
“…In another direction, the theory developed in this paper is interesting because of the reduction of elasticity to a Stokes framework. After an appropriate combination with viscous degrees of freedom, remaining in a similar framework, this could open simple ways to model viscoelastic substrate, and thus to address the complex behaviours reported in recent stick-slip wetting experiments [13][14]24]. The next step would then consist in including the possible flow of the liquid inside the substrate (permeation, swelling) which also leeds to specific wetting effects, as discussed recently by Kajiya et al [19], or the effect of a surfactant at the free surface which has also motivated several experimental studies on gel substrates [10][11][12]16] with puzzling self-organisation phenomena, still not well understood.…”
Section: -Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another direction, the theory developed in this paper is interesting because of the reduction of elasticity to a Stokes framework. After an appropriate combination with viscous degrees of freedom, remaining in a similar framework, this could open simple ways to model viscoelastic substrate, and thus to address the complex behaviours reported in recent stick-slip wetting experiments [13][14]24]. The next step would then consist in including the possible flow of the liquid inside the substrate (permeation, swelling) which also leeds to specific wetting effects, as discussed recently by Kajiya et al [19], or the effect of a surfactant at the free surface which has also motivated several experimental studies on gel substrates [10][11][12]16] with puzzling self-organisation phenomena, still not well understood.…”
Section: -Conclusionmentioning
confidence: 99%
“…Wetting of a deformable solid has been investigated long ago by many authors [1][2][3][4][5][6][7][8][9], and is presently attracting again a great attention [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Experimental studies are still very active on different soft substrates (elastomers, gels, polymers…) [10][11][12][13][14][15][16][17][18][19][20] in a field having potentially a large number of applications (soft lenses, biomaterials, low friction surfaces…), while new insights have been provided recently in the modelling of contact lines on soft substrates [18,[20][21][22][23]. In the original vision, developed by de Gennes and Shanahan [3][4][5], it is known that a "ridge" is formed by the liquid surface tension γ pulling the substrate near the contact line, whose dimensions scale as γ/E , E being the Young modulus of the substrate (see fig.1).…”
Section: -Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the spreading and wetting phenomena are intertwined and together build the foundation of many industrial applications from oil recycling to microfluidics and nanoprinting . It is worth noting that based on eq , the extreme CAs of 0° and 180° can define two regimes of total ( S>0) and partial ( S<0) wetting, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, they did not manage to image the deformation of the solid-liquid interface. Applying an optical profilometry, Pu et al analysed the entire profile of the wetting ridge near the TPCL formed in a series of experiments, including dip-coating [59][60][61], sliding [62] and evaporation [63] of sessile droplets on soft viscoelastic substrates. It was found that substrate deformation manifests its shape and profile as changes in the contact angle as the droplet volume is increased or reduced.…”
Section: Experimental Observationsmentioning
confidence: 99%